Comparative pharmacokinetics of carumonam and aztreonam in mice, rats, rabbits, dogs, and cynomolgus monkeys. - Kita, Y (1986)
The pharmacokinetic properties of carumonam (AMA-1080, Ro 17-2301) were studied in mice, rats, rabbits, dogs, and cynomolgus monkeys and compared with those of aztreonam. Carumonam administered subcutaneously in mice or intramuscularly in rats, rabbits, dogs, and cynomolgus monkeys at a dose of 20 mg/kg was readily absorbed and distributed at high concentrations in the plasma, kidneys, liver, and lungs, as was aztreonam. The peak level of carumonam in plasma, ranging from 41 micrograms/ml in mice to 68 micrograms/ml in monkeys; the area under the plasma concentration-time curve, ranging from 20 micrograms X h/ml in mice to 80 micrograms X h/ml in monkeys; the plasma half-life, ranging from 0.24 h in mice to 1.10 h in dogs; and the plasma clearance, ranging from 4.5 ml/min per kg in monkeys to 16.7 ml/min per kg in mice, resembled respective values of aztreonam. In rats, carumonam was eliminated faster than aztreonam. The levels of both antibiotics in the kidneys and liver were usually higher than respective levels in plasma. The level of carumonam in the kidney was usually higher than that of aztreonam, whereas the level of aztreonam in the liver was usually higher than that of carumonam. Both antibiotics showed similar distribution in the lung and spleen; the levels in these tissues were less than the levels in plasma. Carumonam was excreted mainly in the urine; the recovery ranged from 52% (from dogs) to 73% (from rabbits). The urinary recovery of carumonam from mice, rats, and monkeys was higher, but the recovery of carumonam from rabbits and dogs was lower than that of aztreonam. The biliary excretion of carumonam, amounting to 4.1% from rats and less than 0.3% from rabbits and dogs, was smaller than that of aztreonam, amounting to 19.1% from rats and around 1% from rabbits and dogs. The extent of protein binding at 20 micrograms of carumonam per ml was lower than that of aztreonam. For all species except dogs, which have very low binding in their serum (11% for carumonam and 20% for aztreonam), the binding of carumonam ranged from 21% (in rabbits) to 36% (in rats), whereas that of aztreonam ranged from 55% (in rabbits) to 85% (in rats). Thus, the plasma pharmacokinetics of carumonam and aztreonam were generally similar for all animals tested except dogs, but the two antibiotics differed slightly in their distribution in tissue, excretion, and protein binding in serum.